Implementasi Gerakan Literasi Sekolah Untuk Meningkatkan Minat dan Kemampuan Membaca Melalui Program Jam Baca Model Teras Pustaka Bagi Warga Sekolah SD 8 Kandangmas - Mulyono Mulyono (Lembaga Pendidikan Hikmatun Najah Blora, 2021)
The purpose of this study is to describe the implementation of the school literacy movement to increase interest and reading skills through the library terrace model reading hour program for school residents of SD 8 Kandangmas. This type of research is School Action Research (PTS). This research was conducted at SD 8 Kandangmas. Data collection techniques are interviews, observation and documentation. The results of this study in Cycle I obtained an observation of interest for teachers with an average score of 71. While for education staff from 5 education personnel the average value was 68, while interest in students obtained an average value of 75. In cycle II, for teachers the average value was 85. Interest scores for education staff the average is 84. For students the average value is 89. Judging from the average value in interest in literacy in cycle II, there is an increase of 20% from the average in cycle I. Meanwhile, literacy skills, especially the ability to read non-textbooks, are obtained from the average literacy reading ability in the second cycle was found to be an increase of 12% from the first cycle.Tujuan Penelitian ini yaitu untuk mendeskripsikan implementasi gerakan literasi sekolah untuk meningkatkan minat dan kemampuan membaca melalui program jam baca model teras pustaka bagi warga sekolah SD 8 Kandangmas. Jenis penelitian ini yaitu Penelitian Tindakan Sekolah (PTS). Penelitian ini dilaksanakan di SD 8 Kandangmas. Teknik pengumpulan data adalah wawancara, observasi dan dokumentasi. Hasil penelitian ini pada Siklus I didapat nilai pengamatan minat untuk guru nilai rerata 71. Sedangkan pada tenaga kependidikan dari 5 tenaga kependidikan nilai rerata 68, sedangkan minat pada siswa diperoleh nilai rerata 75. Pada siklus II, untuk guru nilai nilai rata-rata 85. Nilai minat untuk tenaga kependidikan rata-rata 84. Untuk siswa nilai rata-rata 89. Dilihat dari nilai rata-rata pada minat berliterasi siklus II ada kenaikan sebesar 20% dari rata-rata siklus I. Sedangkan kemampuan berliterasi khususnya kemampuann membaca non buku teks didapat dari rata-rata pada kemampuan membaca literasi siklus II didapat kenaikan 12% dari siklus I.